(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2014)
With the advent of the globalization, the rapid development in technology and the intensity of competition companies attemptto maintain competition advantages and retain customers. The traditional methods in managerial accounting become irrelevance to achieve the objectives of these companies especially with the rapid changes in modern manufacturing environment .Thus there is a need to new tools in accounting such as lean accounting, which is considered as a costing method that support creating value for the customer by costing the entire value stream, eliminating waste in the accounting process, reduced lead time, improved quality, lowered time delivery and increased available capacity. Using value stream focuses not only on the waste but also determining the sources of waste in value stream. So business manufacturing waste that occurs in the process can be easily identified. Thus the objective of the research is to bring out the concept, principles, tools and objectives of lean accounting and to discuss the issue of lean accounting as a replacement of the traditional accounting systems for cost accounting, management accounting and external financial reports. Also one of the objectives of the research is to show the procedures applied in the sample company :AL-Hayat soft drinks & Mineral Water Company. The research depends on two aspects :The Theoretical aspect which depends on references such as: books, researches ,internet and the practical aspect depends on the important formal documents of the company. This research has reached asset of conclusions of the most important: 1-Standard costing, absorption costing, activity based costing and other traditional cost accounting do not fit in with a lean accounting system because of the complexity in accounting processes of traditional systems and a high cost incurred. Just as stated in the first hypothesis of the alternative hypothesis H1. 2-Time saved over traditional manufacturing by using lean accounting in comparison with traditional manufacturing process in the sample company is 1593.2 minutes (2683.2 min-1090 min), so the company can use this available time to produce 318.64 (50 packs) or 1593.2minutes/ 5 minutes (1+1+1+1+1).just as stated in the third hypothesis of the alternative hypothesis H1. 3-The redundant number of employees in the manufacturing process in the sample company is 7 employees, the average monthly salaries of the employees in the manufacturing process is 676 so the company can save 4732 (676 x7 employees) ,then we can deduce that implementing the value stream structure does not require an increase in the number of people needed but on the contrary it reduces the demand for people. Just as stated in the third hypothesis of the alternative hypothesis H1. 4-Financial and non-financial information in the box scorecard of the sample company tell managers how well they doing and help them as planning ,control and future decision making tools about the whole activities (operational, capacity, financial) of the company. Just as stated in the second hypothesis of the alternative hypothesis H1. The most important recommendations that emerged from the research are summarized as follows: • Conversions from traditional accounting to lean manufacturing and lean accounting requires publishing concepts of lean accounting among employees and educate them by organizing training courses about the modern techniques of managerial accounting and requirements to apply and implement lean manufacturing. 2-The sample company has to re-arrange the manufacturing processes for the purpose of achieving the optimum flow of operations. 3-The sample company has to reconsider the number of employees working in the manufacturing processes. 4-The sample company has to take advantage of preparing income statement according to value stream costing,and preparing box score card that contains financial and non-financial information in three dimensions.